Factors influencing male involvement in prevention of mother-to-child transmission services in Khayelitsha, Cape Town, South Africa - Ladur, Alice Norah (Department of Public Health and Family Medicine, 2015)
This study sought to explore the role of men in the prevention of mother-to-child transmission services in Khayelitsha, South Africa. Two focus group discussions were held with 25 men of unknown status and one focus group discussion held with 12 HIV-positive women in the community. In-depth interviews were also conducted with four HIV-positive couples and five service providers purposely sampled from the community and a health facility, respectively.